Climate Basics, Climate Information Service, Climate Risk Management Training Guide - Terefe, Tadesse; Dejene, Sintayehu W.; Belay, Berhanu; Amha, Yosef; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate Basics, Climate Information Service, Climate Risk Management Training Guide